Gender, sexuality and violence in organizations : the unspoken forces of organization violations - Hearn, Jeff, 1947- (SAGE, 2001)
This text brings together the themes of gender, sexuality violence and organisations. The authors offer insights into violence and abuse gleaned through feminist research and apply them to organisational analysis.